(untitled) (San Francisco, 2006)
Results That Matter will provide a new governance framework for using valuable tools of community improvement—especially performance measurement and citizen engagement—to empower communities to achieve the outcomes their citizens most desire. Government and nonprofit managers will learn how to combine these tools in new ways, not only to achieve one-time improvement of their organizations and communities, but to foster continual community renewal and improvement. The benefits and practicality of the framework and related practices will be reinforced by case examples from 25 communities across the country. The book will offer "how to" guidance to public and nonprofit managers, including promising practices for effective communities, and new roles for citizens, community leaders, and managers.
Keywords: Political participation,Community organization,Neighborhood government,Local government,Public-private sector cooperation; United States,United States,United States,United States,United States